PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1942)
Abstract The article presents problems that were presented by the Board of Examiners of the American Institute of Accountants as the second half of the C.P.A. Examination in accounting theory and practice held on November 14, 1941.